(untitled) (Research, Society and Development, 2022)
The objective of this study is to identify the actions of nurses at the intrapartum moment to prevent obstetric violence. This research was a qualitative and descriptive study in the form of an integrative literature review. The sample consisted of scientific articles available in relevant virtual databases in the area, such as SCIELO, VHL, LILACS, BDENF and others. The inclusion criteria established were: articles published in full, made available online without a period of time, written in Portuguese. Materials considered gray literature were excluded. To search for the material in the databases, the Descriptors in Health Sciences (DeCS) “Nursing”, “Obstetric Violence” and “Delivery Work” were used with the Boolean operator “and” and “or”. In the end, 07 (seven) articles were selected that fit the proposed objective of this study. Obstetric violence induces the parturient to feel what is called the pain of dehumanized childbirth, bringing to the same impact and/or implications for her health. In this sense, the objective of the study is to identify the actions of nurses at the intrapartum moment to prevent obstetric violence. It is worth noting that the new technologies of the contemporary world, together with medicalization, have made the moment of childbirth a hospital act, leading the doctor to become the protagonist of such a feat and the process as pathological, so that the professional has been taking responsibility and autonomy during the parturition process.